Rooftop gardening to improve food security in Dhaka city: A review of the present practices - Chowdhury, Mohammad Hasan; Eashat, Md. Fahim Sharker; Sarkar, Chinmoy; Purba, Nafisa Habib; Habib, Mohammad Asadul; Sarkar, Plabon; Shill, Lincon Chandra (International Multidisciplinary Research Journal, 2020)
In recent years, the trend of growing vegetables on green roofs has gained momentum as a way of promoting agricultural sustainability in Dhaka City. Rooftop gardens become an important part of urban agriculture's recent rejuvenation and offer alternative spaces for urban markets to grow vegetable products. Green roofs create spaces for vegetable crop production, thereby creating opportunities for agricultural incorporation into urban communities. At present, however, vegetable production activities on rooftops are limited due to multiple challenges that need to be addressed before widespread implementation takes place. Rooftop agriculture can improve various ecosystem services, enhance the biodiversity of urban areas and reduce food insecurity. Food production from green roofs will help support and sustain food for urban communities and provide a rare opportunity to grow food efficiently in typically unused spaces. As human populations become more urbanized and urban consumers become more interested in local food for their families, the use of alternative agricultural production systems, such as green roof technologies, will increase in importance. While cultivating food on buildings is a key component of making cities more sustainable and habitable, green roofs are not the total solution for providing cities with food security. They should be viewed more as a supplement to other sources of food production in urban areas.